2021
DOI: 10.3390/ijerph18042030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Fatigue after COVID-19 in Non-Hospitalized Subjects: A Population-Based Study

Abstract: This study assessed the prevalence and determinants of fatigue in a population-based cohort of non-hospitalized subjects 1.5–6 months after COVID-19. It was a mixed postal/web survey of all non-hospitalized patients ≥18 years with a positive PCR for SARS-CoV-2 until 1 June 2020 in a geographically defined area. In total, 938 subjects received a questionnaire including the Chalder fatigue scale (CFQ-11) and the energy/fatigue scale of the RAND-36 questionnaire. We estimated z scores for comparison with general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
102
3
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 48 publications
20
102
3
7
Order By: Relevance
“…Furthermore, a multivariable analysis adjusting for gender, ethnicity, age, BMI, and hospitalisation status reported that only the presence of fatigue accounted for long-term activity impairment (OR 6¢0, 95% CI 1¢0À34¢9) [29]. Similarly, those with a higher symptom load during the initial infection had greater odds of persistent fatigue [30].…”
Section: Predictors Of Post-covid Syndromementioning
confidence: 99%
“…Furthermore, a multivariable analysis adjusting for gender, ethnicity, age, BMI, and hospitalisation status reported that only the presence of fatigue accounted for long-term activity impairment (OR 6¢0, 95% CI 1¢0À34¢9) [29]. Similarly, those with a higher symptom load during the initial infection had greater odds of persistent fatigue [30].…”
Section: Predictors Of Post-covid Syndromementioning
confidence: 99%
“…Similarly, it is unknown if SARS-COV-2 infection exacerbates preexisting neuropathies (e.g., diabetic neuropathy) Long-lasting and disabling fatigue is another frequently reported symptom under the umbrella of long COVID (Table 2, Appendix Table 2) [162,163]. Based on recent cohort studies, the frequency of fatigue and/or muscular weakness at 6 months post-symptom onset can reach 60% [162,164,165]. Intensity can fluctuate, it is typically exacerbated by physical or mental effort, it seems to affect mostly young women although exact frequency is hard to ascertain due to reporting bias.…”
Section: Chronic Pain/chronic Fatiguementioning
confidence: 99%
“…The three-week inpatient PR program was performed in accordance with the recommendations of the German Respiratory Society (Deutsche Gesellschaft für Pneumologie) for PR in patients with COVID-19 [13]. The program was tailored to each patient's individual needs and included the following rehabilitative therapy components (O = obligatory for all participants, except those with individual contraindications, F = facultative if needed):…”
Section: Interventionmentioning
confidence: 99%
“…Particularly after severe or critical courses, i.e., after hospitalization, clinical manifestations often (up to 76% [6-9]) do not regress after the acute phase of the disease, so many patients still suffer both physically and psychologically from persistent impairments after an acute infection [6-8, 10]. In addition, although it is less common, even after initially milder courses that could be treated on an outpatient basis, symptoms can persist over time [11][12][13][14]. The term postacute COVID-19 syndrome (PACS) has been proposed to describe the presence of persistent signs and symptoms beyond 4 weeks after the onset of symptoms in patients with current negative polymerase chain reaction (PCR) test results [10].…”
mentioning
confidence: 99%